(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
Due to the fact that irony is one of the stylistic device which is used for ensuring effective intercultural communication. Teaching English language is easier to explain if a teacher gives various irony in mother tongue and depicted in L2. The article is devoted to characterize the irony giving some relevant example.